2011
DOI: 10.1128/jvi.02399-10
|View full text |Cite
|
Sign up to set email alerts
|

A Respiratory Syncytial Virus Replicon That Is Noncytotoxic and Capable of Long-Term Foreign Gene Expression

Abstract: Respiratory syncytial virus (RSV) infection of most cultured cell lines causes cell-cell fusion and death. Cell fusion is caused by the fusion (F) glycoprotein and is clearly cytopathic, but other aspects of RSV infection may also contribute to cytopathology. To investigate this possibility, we generated an RSV replicon that lacks all three of its glycoprotein genes and so cannot cause cell-cell fusion or virus spread. This replicon includes a green fluorescent protein gene and an antibiotic resistance gene to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 59 publications
0
28
0
Order By: Relevance
“…The MT4 cell line was obtained from the NIH AIDS Research and Reference Reagent Program (Germantown, MD) and cultured in RPMI 1640 medium (Irvine Scientific) supplemented with 10% FBS, 100 units/ml penicillin, 100 units/ml streptomycin, and 2 mM L-glutamine. RSV replicon BHK cells (19) were grown in MEM (1ϫ) containing GlutaMAX with Earle's salts (Life Technologies), 10% HI-FBS, 10 units/ml penicillin, 10 g/ml streptomycin, and 50 g/ml blasticidin S. Air-liquid-interface differentiated primary normal human airway epithelial (HAE) cells were obtained from MatTek Corporation (AIR-100 kit). The HAE cells were derived from trachea and mainstem bronchi of lung tissue donated with informed consent for research purposes at the time of death.…”
Section: Cell Culture and Viruses Hep-2 Cells (Ccl-23) And A549 Cellmentioning
confidence: 99%
See 1 more Smart Citation
“…The MT4 cell line was obtained from the NIH AIDS Research and Reference Reagent Program (Germantown, MD) and cultured in RPMI 1640 medium (Irvine Scientific) supplemented with 10% FBS, 100 units/ml penicillin, 100 units/ml streptomycin, and 2 mM L-glutamine. RSV replicon BHK cells (19) were grown in MEM (1ϫ) containing GlutaMAX with Earle's salts (Life Technologies), 10% HI-FBS, 10 units/ml penicillin, 10 g/ml streptomycin, and 50 g/ml blasticidin S. Air-liquid-interface differentiated primary normal human airway epithelial (HAE) cells were obtained from MatTek Corporation (AIR-100 kit). The HAE cells were derived from trachea and mainstem bronchi of lung tissue donated with informed consent for research purposes at the time of death.…”
Section: Cell Culture and Viruses Hep-2 Cells (Ccl-23) And A549 Cellmentioning
confidence: 99%
“…BHK cells containing a stably transformed subgenomic RSV replicon expressing a green fluorescent protein (GFP) reporter cassette were licensed from Apath, LLC (19). Replicon cells were seeded at a density of 10,000 cells/well in black, flat, clear-bottom 96-well plates (Corning) and cultured overnight in growth media containing 50 g/ml blasticidin S. The growth medium was aspirated and replaced with 200 l of 3-fold serially diluted compounds prepared in 2% HI-FBS media containing 50 g/ml blasticidin S. After 3 days at 37°C, the cells were fixed using 4% paraformaldehyde (PFA) supplemented with Hoechst dye (Invitrogen).…”
Section: Cell Culture and Viruses Hep-2 Cells (Ccl-23) And A549 Cellmentioning
confidence: 99%
“…However, high levels of the hRSV-F protein, as well as its secreted form, could be expressed from a codon-optimized hRSV-F sequence. For the immunization in the presented study, the secreted form of hRSV-F was used as a vaccine antigen since expression of a fusion active full-length hRSV-F was shown to be cytotoxic (18). Consistent with other studies (19,20), we had previously observed that immunization with DNA or adenoviral vectors (AdV) vaccines expressing the soluble hRSV-F protein, resulted in a superior immune response and protective efficacy in mice, which opened the possibility to further explore these genetic vaccines against hRSV in NHPs (21,22).…”
mentioning
confidence: 99%
“…21 The replicon cell line used in this screen uses a modified viral genome encoding these proteins essential for viral replication. Viral proteins associated with viral entry and RSV-induced cytotoxicity such as the viral fusion (F) protein, attachment glycoprotein (G), and small hydrophobic (SH) glycoprotein are removed and replaced with a luciferase reporter gene.…”
Section: Discussionmentioning
confidence: 99%